2020
DOI: 10.1038/s41598-020-64525-z
|View full text |Cite
|
Sign up to set email alerts
|

The polygenic architecture of left ventricular mass mirrors the clinical epidemiology

Abstract: Left ventricular (LV) mass is a prognostic biomarker for incident heart disease and all-cause mortality. Large-scale genome-wide association studies have identified few SNPs associated with LV mass. We hypothesized that a polygenic discovery approach using LV mass measurements made in a clinical population would identify risk factors and diseases associated with adverse LV remodeling. We developed a polygenic single nucleotide polymorphism-based predictor of LV mass in 7,601 individuals with LV mass measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…A GWAS did not identify common SNPs significantly associated with G1DD status, consistent with prior studies examining diastolic function phenotypes. 16 , 17 However, several of the top SNPs had appeared to have relevance to cardiometabolic phenotypes and the left ventricle. Thus, we examined associations with genetic predictors of established risk factors, which is a more powered approach to detect weak associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A GWAS did not identify common SNPs significantly associated with G1DD status, consistent with prior studies examining diastolic function phenotypes. 16 , 17 However, several of the top SNPs had appeared to have relevance to cardiometabolic phenotypes and the left ventricle. Thus, we examined associations with genetic predictors of established risk factors, which is a more powered approach to detect weak associations.…”
Section: Discussionmentioning
confidence: 99%
“… 16 However, structural traits related to diastolic function, such as left ventricular mass and other functional left ventricular measures, have been demonstrated to have a significant heritable component based on common SNPs. 17 , 18 This could suggest that diastolic dysfunction is a genetically heterogeneous phenotype representing the accumulated contributions from many risk mechanisms.…”
mentioning
confidence: 99%
“…With the progress in genome-wide association (GWAS) analysis in recent years, genomics has made considerable progress in the prediction of complex human diseases, such as CAD and AF [32]. To date, over 50 pathogenic gene mutations have been revealed to cause AF, which mainly involve cellular signal molecules [33], myocardial structural proteins [34], ion [35] and gap junction channels [36]. Hsu et al [34] reported that subjects with AF carrying the ALDH2*2 polymorphism showed more severe oxidative stress in their atria compared with non-carriers and suggested that ALDH2 may protect from AF-related OR in adjusted model was adjusted for LAD, LVDd, LVSd, LVEF, ALT, AST, UN, Scr, UA, CAD, HF, use of ACEIs, BBs, MRAs, digoxin and diuretics OR: odds ratio; CI: confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) of echocardiography-based LVM identified a single susceptibility locus downstream of SPCS3 . 79 More recently, a genome-wide association study within 19,000 individuals 10 identified significant variants in the gene TTN associated with CMR-based LVM.…”
Section: Introductionmentioning
confidence: 99%